Schwannomatosis: a genetic and epidemiological study. Issue 11 (16th June 2018) - Evans, D Gareth; Bowers, Naomi L; Tobi, Simon; Hartley, Claire; Wallace, Andrew J; King, Andrew T; Lloyd, Simon K W; Rutherford, Scott A; Hammerbeck-Ward, Charlotte; Pathmanaban, Omar N; Freeman, Simon R; Ealing, John; et al.
Abstract : Objectives: Schwannomatosis is a dominantly inherited condition predisposing to schwannomas of mainly spinal and peripheral nerves with some diagnostic overlap with neurofibromatosis-2 (NF2), but the underlying epidemiology is poorly understood. We present the birth incidence and prevalence allowing for overlap with NF2. Methods: Schwannomatosis and NF2 cases were ascertained from the Manchester region of England (population=4.8 million) and from across the UK. Point prevalence and birth incidence were calculated from regional birth statistics. Genetic analysis was also performed on NF2, LZTR1 and SMARCB1 on blood and tumour DNA samples when available. Results: Regional prevalence for schwannomatosis and NF2 were 1 in 126 315 and 50 500, respectively, with calculated birth incidences of 1 in 68 956 and 1 in 27 956. Mosaic NF2 causes a substantial overlap with schwannomatosis resulting in the misdiagnosis of at least 9% of schwannomatosis cases. LZTR1 -associated schwannomatosis also causes a small number of cases that are misdiagnosed with NF2 (1%–2%), due to the occurrence of a unilateral vestibular schwannoma. Patients with schwannomatosis had lower numbers of non-vestibular cranial schwannomas, but more peripheral and spinal nerve schwannomas with pain as a predominant presenting symptom. Life expectancy was significantly better in schwannomatosis (mean age at death 76.9) compared with NF2 (mean age at death 66.2; p=0.004). Conclusions: Within the highly ascertained North-West England population, schwannomatosis has less than half the birth incidence and prevalence of NF2.